Some Aspects of Formation of Architectural Periodicals in Historical Perspective - Irina Ilyinichna Komarova; Andrey Leonidovich Tretyakov (Управленческое консультирование, 2018)
The researchers in this study continue to consider the establishment and development of modern architectural science. We describe the historical background of the formation of the architectural periodicals. It noted the significant role of scientific societies in the development of periodicals in the field of architecture. The necessity of a comprehensive study of the issue in order to present an overall picture of architectural periodicals professional community. Denotes the importance of applying the bibliography as a significant tool of library and information science to represent the architectural science in modern conditions.